Nanotechnology Inspired Advanced Engineering Fundamentals for Optimizing Drug Delivery - Kassem, Ahmed A. (Current Drug Targets, 2018)
Background: Drug toxicity and inefficacy are commonly experienced problems with drug therapy failure. To face these problems, extensive research work took place aiming to design new dosage forms for drug delivery especially nanoparticulate systems. These systems are designed to increase the quantity of the therapeutic molecule delivered to the desired site concurrently with reduced side effects. In order to achieve this objective, nanocarriers must principally display suitable drug vehiculization abilities and a controlled biological destiny of drug molecules. Only the intelligent design of the nanomedicine will accomplish these fundamentals. Methods: The present review article is dedicated to the discussion of the important fundamentals to be considered in the fabrication of nanomedicines. These include the therapeutic agent, the imaging agent, the nanocarrier and the functionalization moieties. Special consideration is devoted to the explanation and compilation of highly potential fabrication approaches assisting how to control the in vivo destiny of the nanomedicine. Finally, some nanotechnology-based drug delivery systems, for the development of nanomedicine, are also discussed. Results: The nanotechnology-based drug delivery systems show remarkable outcomes based on passive and active targeting as well as improvement of the drug pharmacodynamic and pharmacokinetic profiles. Multifunctional nanocarrier concept affords a revolutionary drug delivery approach for maximizing the efficacy, safety and monitoring the biological fate of the therapeutic molecule. Conclusion: Nanomedicines may enhance the efficacy of therapeutic molecules and reduce their toxic effects. Meanwhile, further research works are required to rightly optimize (and define) the effectiveness, nanotoxicity, in vivo destiny and feasibility of these nanomedicines which, from a preclinical standpoint, are actually promising.
Keywords: nanoparticulate drug delivery system